Everyday problem-based learning : quick projects to build problem-solving fluency - Pete, Brian M.; Fogarty, Robin (ASCD, 2018)
Brian Pete and Robin Fogarty present ways to use problem-based learning as a daily approach to helping students learn authentic and relevant skills.